Pengaruh Metode Reward dan Punishment Terhadap Perkembangan Moral Siswa Sekolah Dasar - Nayla Rizqiyah; Triana Lestari (Universitas Muhammadiyah Enrekang, 2021)
Technological pedagogical content knowledge (TPACK) is a relatively new learning model in the world of education. The practice of implementing this method includes mastery of technology, pedagogics and knowledge of learning content. TPACK is involved in the process of developing learning designs, learning models and strategies, assessing and reorganizing linked curriculum and using technology as a reference for educational development. The research was conducted using structured interviews with students at several universities and the results of the research were described using a qualitative descriptive method. The relationship between TPACK and modernization in the world of education are two things that cannot be separated, the inclusion of technology in the elements of Indonesian education has a significant influence and changes the conventional order with a new method order and is expected to bring Indonesian education to a more advanced direction. It is hoped that the research can provide benefits for developing the field of the education system as well as additional information for other research.